Surgical Embolectomy for Acute Massive and Submassive Pulmonary Embolism in a Series of 115 Patients - Neely, Robert C; Byrne, John G; Gosev, Igor; Cohn, Lawrence H; Javed, Quratulain; Rawn, James D; Goldhaber, Samuel Z; Piazza, Gregory; Aranki, Sary F; Shekar, Prem S; Leacche, Marzia (The Annals of thoracic surgery, 2015)
Pulmonary embolectomy is often indicated for central pulmonary embolism (PE) with hemodynamic instability, but remains controversial for hemodynamically stable patients with signs of right ventricular dysfunction. Because thrombolytic therapy is often contraindicated postoperatively, we reviewed risk factors and outcomes of pulmonary embolectomy for stable and unstable central PE, particularly in the early postoperative period. Between October 1999 and September 2013, 115 patients underwent pulmonary embolectomy for central, hemodynamically unstable PE (49 of 115, 43%) or hemodynamically stable PE (56 of 115, 49%). Ten operations for alternate indications (right atrial mass, endocarditis) were excluded for comparison analysis, leaving 105 patients. Mean age was 59 ± 13 years; 46 of 105 patients (44%) had recent surgery (within 5 weeks): orthopedic (12 of 46, 25%), neurosurgery (11 of 46, 24%), or general surgery (10 of 46, 22%). Preoperative demographics did not differ between groups, except for the frequency of cardiopulmonary resuscitation among unstable patients (11 of 49, 22%) versus stable patients (0 of 56, 0%; p < 0.001). Operative mortality for the combined groups was 6.6% (7 of 105): unstable 10.2% (5 of 49) versus stable 3.6% (2 of 56; p = 0.247). Of 11 patients requiring preoperative cardiopulmonary resuscitation, 4 died. Six-month, 1-year, and 3-year survival rates were, respectively, 75%, 68.4%, and 65.8% for unstable PE, and 92.6%, 86.7%, and 80.4% for stable PE (p = 0.018). This large series of pulmonary embolectomies demonstrates excellent early and late survival rates for patients with stable PE and unstable PE. These findings confirm pulmonary embolectomy as a beneficial therapeutic option for central PE, especially during the postoperative period when thrombolytic therapy is often contraindicated.